Relationship between Maternal ABO Blood group and pregnancy complications of adichunchanagiri hospital B.G Nagara -A cross sectional study (Panacea Journal of Medical Sciences, 2023)
Background: ABO blood group has been divulged as a risk factor for perceptible diseased states. The ABO blood group differences may put a patient at specific risk according to their inherited antigens among the obstetrical syndromes like Intrauterine growth restriction, Pre-eclampsia and pre-term labour. Studies conducted have shown Group O individuals had lowest plasma von Willebrand factor and non O group had elevated level of this factor which showed increased thrombotic risk among these individuals. The earlier studies conducted have focused only on preeclampsia but not on other complications of pregnancy and the data available is scarce. The study aims to determine whether maternal ABO blood groups contribute to adverse pregnancy outcomes especially in this part of the country.